Association Consume Sweet Food with Overweight Adolescents - Siregar, Siti Maisyaroh Fitri; Lubis, Adelina Irmayani; Husna, Arfah; Fera, Dian; Rinawati, Rinawati; Muhsin, Sri Wahyuni; Harahap, Laila Apriani; Nursia, Lily Eki (Universitas Teuku Umar, 2024)
The prevalence of overweight in adolescents is increasing rapidly due to the high production and consumption of sweet foods favored by adolescents. Being overweight during adolescence is correlated with the risk of obesity in adulthood if there is no further prevention. More than one-third of adults and 17% of adolescents are obese, and the prevalence remains stable in America. In Indonesia, the prevalence of excessive nutrition has also reached 16%. This study to determine which types of food consumption are at risk of overweight in adolescents. This research used a cross-sectional design. The study sample consisted of high school students and was selected using random sampling methods. The dependent variable was overweight, and the independent variables included consumption aims of fatty foods, sweet foods, sweet pastries, junk food, and sweet beverages. The gathered data were analyzed using univariate analysis and bivariate analysis with a chi-square test at α = 0.05. This research found that 28% of adolescents are overweight. The results of the bivariate analysis showed that the variables significantly influencing overweight we the consumption of sweet foods (p = 0.02; OR = 2.965, 95% CI = 0.978-8.988) and sweet pastries (p = 0.01; OR = 6.829, 95% CI = 0.987-47.231). In conclusion, the consumption of sweet foods, which implies high sugar intake, is correlated with overweight in adolescents. It is recommended that adolescents limit their consumption of sweet foods containing high sugar levels and increase their nutritional literacy because there is no recommended dietary allowance for sugar